Muscular collision chess: a qualitative exploration of the role and development of cognition, understanding and knowledge in elite-level decision making. Issue 3 (4th May 2022) - Collins, Rosie; Collins, Dave; Carson, Howie J.
ABSTRACT: Decision making (DM) is a crucial part of team invasion games. The role of context and how this drives both initial DM and primes in-action planning and execution, termed contextual priors, has been investigated. Findings suggest a significant role for cognition, which appears to run contrary to some of the suggestions made by an ecological dynamics approach. Wishing to clarify this situation for coaches and psychologists, this research explores the experience of nine top-tier key decision makers in rugby union, using an interview approach. Results showed a wide range of context-based information considered by players during the DM process. Furthermore, this information acted to prime subsequent attention and in-action thinking. Finally, this research sought to understand if, and therefore how, DM could be taught, developed and primed by players and coaches. Our data are supportive of a more cognitively focused approach to developing DM, although our data do not dismiss a role for direct perception in optimising performance. Implications for practice are discussed.